Challenges and opportunities for geospatial integration into ‘trotro’ road travel in Ghana - Gift Dumedah (Journal of Applied Geospatial Information, 2017)
Travel routing is vital for efficient delivery of public and private services and the movement of people and goods. In Ghana, the major nature of travel routing is through the ‘trotro’ system. The trotro system uses an automobile to move people and goods along a prescribed travel route, with locally known stops where people get on and off the vehicle. The trotro system is significant because Ghana's road network and street addressing are imperfectly mapped. Thus, this paper critically evaluates the research challenges and opportunities for the development of an integrated trotro geographic addressing system. The widespread trotro address assignment and the availability of geolocation technology on mobile phones, make the integrated trotro geographic addressing framework an inexpensive and a comprehensive approach. The key research questions that need investigation for the development of such an integrated geographic addressing system are identified, together with a critical review of the problem, and its research challenges and prospects.